Mathematics Teachers’ Perceptions about Problem-Solving: The case of Ghana : Mathematics Teachers’ Perceptions about Problem-Solving: The case of Ghana - Ampadu, Ernest (The Oguaa Educator, 2019)
Most students experience different levels of difficulties in learning mathematics. TIMSS results have shown that most students in Ghana do not perform well in higher level tasks designed to assess applications and non-routine problems. This study, therefore, aimed at examining Ghanaian Junior and Senior High School mathematics teachers problem-solving strategies and their professional development needs about problem-solving. 114 mathematics teachers from 28 Junior High School (JHS) and Senior High School (SHS) in the Cape Coast Metropolis took part in the study. Quantitative and qualitative data were collected using a semi-structured questionnaire. The results from the study show that although teachers appreciate the importance of problem-solving in improving mathematics teaching and learning, there has not been the needed problem-solving training to support teachers in this regard. The researcher, therefore, argue that despite the numerous advantages associated with problem-solving strategy of teaching and learning, continuous professional development training for teachers should be paramount in our quest for helping students develop problem solving skills. Ghanaian JHS and SHS students can be in a disadvantageous position as they compete with their peers from other countries in international comparison examinations if our teachers are not given the needed support to become proficient in the use of problem-solving strategies in the classrooms.